SYNTHESIS, GRAVIMETRIC ANALYSIS AND ANTIMICROBIAL STUDIES OF TRANSITION METALS (Cu(II), Zn(II)) COMPLEXES OF SCHIFF DERIVED FROM 2-HYDROXY-1-NAPHTHALDEHYDE AND 2-AMINO-3-METHYLPYRIDINE (FUDMA JOURNAL OF SCIENCES, 2022)
The interaction between 2-hydroxy-1-naphthaldehyde with 2-amino-3-methylpyridine give an orange- yellow Schiff base and its metals complexes of Cu (II) and Zn (II) were green and dark-green respectively, both Schiff base and metals complexes were characterized using different analytical techniques such as melting point, solubility test, conductivity, measurement, magnetic susceptibility measurement, IR spectroscopy and TGA. The Schiff base and its respective metal complexes showed a sharp melting point and are soluble in ethanol, dimethylsulfuroxide and methanol but insoluble in water and slightly soluble in other solvent. The conductivity value obtained revealed that the synthesized complexes are non-electrolytes while an octahedral geometry was suggested for all complexes based on the data obtained from magnetic susceptibility analysis. The IR results revealed bands at 1596 cm-1 indicating the formation of azomethine (C=N) confirming the formation of Schiff base. 747 cm-1, 773 cm-1, for (M-N) while 465 cm-1, 469 cm-1 for (M-O) bands in the spectra of the complexes supporting coordination of Schiff base to respective metals. The thermo-gram (TGA) data of all complexes, exhibited three stages of decomposition which include loss of water, decomposition of the complexes and the formation of metal (II) oxide as the final product/residue. The in vitro antimicrobial screening of Schiff base and its metals complexes showed that they are potent antimicrobial agents against the tested microorganisms
Keywords: synthesis, gravimetry, antimicrobial, activities, transition metals